PENATAAN LAHAN PARKIR DI PASAR MELATI PURING PARIT BARU KECAMATAN SUNGAI RAYA KABUPATEN KUBU RAYA - Dani, Imran; AS, Syafaruddin; ., Sumiyattinah (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2015)
Kubu Raya district territory is quite a strategic place because it is adjecent with Pontianak City (South east pontianak). Kubu raya District is really potent in the field of trade, with the growth of the economy, comes the need of physical tools in kubu raya district mount up which directly or indirectly cause the use of spacial terrain including physical embodiment and vessel of kubu raya distric, where providing infrastructures should be in line towards the the development of the region in kubu raya district. Sungai Raya subsistrict is the capital region of Kubu Raya which is developing especially in the field of trade with that field itself growing, it makes the population in sungai raya grow accordingly to the daily needs. Thus, a place for trading we know as traditional market is needed for the citizens of sungai raya. As for the purpose of writing this thesis is to know is the parking space that is available able to to accomodate the amount of vehicle that is parked, and to structure the parking space in Melati puring parit baru traditional market. In this research the data that is got is aquired aquired from a couple of firm, that is the BPS and Bappeda of Kubu raya district. The aquirred data are from survei's that is done on sundays (6 April 2014) and mondays (7 April 2014) from 05.00-17.00 Indonesia Local Time with division points as mich as 3. The research wil be calulated an analysed so the need of parking space will be found out. Based on the result of the research, the total of vehicle movement that comes in to the parking location is, for motorcycles its 1787 vehicles, and cars its 135 vehicles. obtained from the calculation is the time duration between 30-60 minute has an intensity that is quite high, so we can conclude that the duration for parking in the research area is approximatly = 1 hour. and for the requirement space in the melati puring parit baru traditional market in kubu raya district obtained at the first point is 4 spaces for cars, and 81 spaces for motorcycle, at the second point is 2 spaces for cars andÂ  and 10 spaces for motorcycles and at the third point is 3 spaces for cars and 14 spaces for motorcycles. concluded rom the needed parking space available is the lack of parking space for cars at point 1 is three parking space, at point 2 one parking space, and point 3 two parking space. To meet the shortage of car parking space the empty motorcycles spaces are used. Keywords: accumulated parking, parking duration, parking turnover, indices parking, and a parking space requirements.